Semi-annual, annual and Universal Time variations in the magnetosphere and in geomagnetic activity: 3. Modelling - Lockwood Mike; Owens Mathew J.; Barnard Luke A.; Watt Clare E.; Scott Chris J.; Coxon John C.; McWilliams Kathryn A. (Journal of Space Weather and Space Climate, 2020)
This is the third in a series of papers that investigate the semi-annual, annual and Universal Time variations in the magnetosphere. In this paper, we use the Lin et al. (2010) empirical model of magnetopause locations, along with the assumption of pressure equilibrium and the Newtonian approximation of magnetosheath pressure, to show that the equinoctial pattern arises in both the cross-tail current at the tail hinge point and in the total energy stored in the tail. The model allows us to study the effects of both dipole tilt and hemispheric asymmetries. As a test of the necessary assumptions made to enable this analysis, we also study simulations by the BATSRUS global MHD magnetosphere model. These also show that the reconnection voltage in the tail is greatest when the dipole tilt is small but this only applies at low solar wind dynamic pressure pSW and does not, on its own, explain why the equinoctial effect increases in amplitude with increased pSW, as demonstrated by Paper 2. Instead, the effect is consistent with the dipole tilt effect on the energy stored in the tail around the reconnection X line. A key factor is that a smaller/larger fraction of the open polar cap flux threads the tail lobe in the hemisphere that is pointed toward/away from the Sun. The analysis using the empirical model uses approximations and so is not definitive; however, because the magnetopause locations in the two hemispheres were fitted separately in generating the model, it gives a unique insight into the effect of the very different offsets of the magnetic pole from the rotational pole in the two hemispheres. It is therefore significant that our analysis using the empirical model does predict a UT variation that is highly consistent with that found in both transpolar voltage data and in geomagnetic activity.